Promoting Maritime Entrepreneurship and Innovation Through Applied Management Studies In Port, Shipping, and Logistics - Jaja Suparman; Marihot Simanjuntak; Muhammad Sayakfika; Faisal Aswin; Andriyan Hendry Ole; Hotman Tua Pangaribuan (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study investigates how applied management studies can foster entrepreneurship and innovation in maritime institutes, particularly in port, shipping, and logistics. By focusing on the qualitative experiences of five maritime professionals, five lecturers, and five graduates, this research explores how technical, promotional, marketing, and innovation strategies impact entrepreneurial development within the maritime industry. A qualitative research approach, supported by descriptive analysis, was employed to assess the effectiveness of applied management studies in promoting entrepreneurship among students. Results demonstrate a high level of efficiency and effectiveness, scoring 9/10 across various indicators. These findings offer insights into how maritime institutes can align their curriculum with industry needs, encouraging innovative and entrepreneurial thinking in future maritime professionals.